(untitled) - Dowd, Steven B. (Philadelphia, 1999)
The latest edition of this text presents both theory and clinical practice of radiation protection and radiobiology -- from X-ray production and nuclear medicine to radiation therapy. Updated to reflect recent regulations, this text serves as a complete review for national certification exams as well as a useful review for clinical practice.
Keywords: Radiation,Medical physics,Radiobiology,Radiation protection,Radiation effects,Radiation Injuries; Safety measures,Methods,Prevention and control